The role of transketolase in the immunotherapy and prognosis of hepatocellular carcinoma: a multi-omics approach - Gu, Xuan-Yu; Zhou, Zheng-Jun; Yao, Hua; Yang, Jia-Li; Gu, Jin; Mu, Rui; Zhao, Li-Jin (Frontiers in Immunology, 2025)
ObjectiveTo explore the role of transketolase (TKT) in the immunotherapy and prognosis of hepatocellular carcinoma (HCC).Materials and methodsTKT expression across various cancers and its associations with tumor immunity and prognosis were analyzed using nomogram models. A multi-omics approach was employed, including bulk RNA-seq analysis, methylation profiling, single-cell analysis, and spatial transcriptomics. Experimental methods included RT-qPCR, siRNA transfection, luciferase reporter assay, and chromatin immunoprecipitation.ResultsTKT was significantly upregulated in multiple cancers and correlated with immune cell infiltration, particularly in HCC. Elevated TKT expression was associated with poor overall survival (OS) in HCC and was an independent prognostic factor (p < 0.05). Drug sensitivity analysis suggested that higher TKT expression was associated with reduced sensitivity to several chemotherapeutic agents, including sorafenib (p < 0.01). Furthermore, hypermethylation of the TKT promoter and low TKT expression were linked to improved OS in HCC (log-rank test p = 0.005). Single-cell analysis revealed that TKT was predominantly expressed in the monocyte/macrophage cluster associated with HCC, and pseudo-time series analysis highlighted TKT’s role in cell differentiation within this cluster. Spatial transcriptomics confirmed the close association between TKT and macrophage distribution in HCC. Moreover, STAT3 was found to directly regulate TKT expression by binding to its promoter region.ConclusionOur findings suggest that TKT may play a role in tumor immunity and prognosis in HCC. Although these results provide insights into the potential involvement of TKT in immune cell infiltration and survival outcomes, further studies are required to fully elucidate its role in immunotherapy.